ORGANIZATIONAL AND FINANCIAL SUPPORT FOR CROSS-BORDER COOPERATION IN THE CONTEXT OF EUROPEAN INTEGRATION AND REGIONAL DEVELOPMENT: THE EXPERIENCE OF ZAKARPATTIA REGION - GOLOVCHANSKA, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the theoretical and practical foundations of organizational and financial support for cross-border cooperation in the context of intensified European integration processes and regional development in Ukraine. The emphasis is placed on determining the role of cross-border interaction as a strategic instrument for spatial integration, strengthening intergovernmental partnership, and socio-economic development of border areas. The article summarizes the current challenges and barriers that hinder the effective implementation of joint initiatives in border areas, in particular institutional, regulatory, infrastructural, and financial disparities. The importance of integrating local and regional management structures, Euroregions, civil society organizations, and businesses in the formation of an effective model for managing cross-border cooperation is substantiated. Particular attention is paid to the analysis of financial sources of support for cross-border projects — from local budgets to EU cohesion policy instruments (in particular, Interreg NEXT programs), intergovernmental funds, and international financial institutions. The dynamics of fund mobilization under the 2021–2027 programs are examined, particularly in Zakarpattia Oblast as an example of successful use of geopolitical potential. The results of the region's participation in Interreg programs are analyzed, and project profiles, funding scales, participant composition, and sectoral focus of initiatives are described. The impact of martial law on the functioning of border infrastructure and the possibilities for adapting cross-border cooperation instruments to the conditions of post-war reconstruction are highlighted. The need to develop high-tech checkpoints, multimodal logistics hubs, digitize management processes, and form a new generation of interregional transport and economic ties is emphasized. The prospects for the integration of the Zakarpattia region into the European space through the active use of EU support programs, infrastructure modernization, and strengthening the institutional capacity of local self-government have been proven.
Keywords: cross-border market; European integration; cross-border cooperation; mechanisms; financing; competitiveness; efficiency; institutional development; economic systems; implementation; European experience; international security